PERENCANAAN PELAKSANAAN PEKERJAAN PILE CAP PADA PROYEK PEMBANGUNAN GEDUNG IGD UPT RUMAH SAKIT NYITDAH TABANAN - Esy Armada Putri; Ni Komang Armaeni; I Wayan Gde Erick Triswandana (Jurnal Teknik Gradien, 2023)
Implementation planning in project management is very important. Project implementation planning is a stage applied in project management by setting goals and objectives that must be achieved and determining the policies of all technical and administrative programs so that they can be implemented. Planning the implementation of development projects uses data collection methods with library and documentation techniques, the data obtained is in the form of secondary and primary data. The implementation method in the field uses conventional and mechanical methods to maximize work, one of which is pile cap work. Pile cap is a way to tie the foundation before a column is erected at the top. This pile cap aims to make the location of the column really at the center point of the foundation so as not to cause eccentricity that can cause additional load on the foundation. The pile cap carried out in the UPT Nyitdah Tabanan Hospital IGD Building Construction project uses four types of pile caps and the implementation method in the field uses mechanical methods. The scheduling results in writing this journal use the Precedence Diagram Method (PDM) method. The total duration based on the calculation is 45 days with a Bill Of Quantity (BOQ) including 10% VAT of Rp7,645,657,919.78.